The iSchools movement: positioning LIS studies in the information age - García-Marco, Francisco-Javier (Anuario ThinkEPI, 2009)
The United States iSchools movement for reforming library and information science studies is analyzed as a contribution to the analysis and debate of the LIS education crisis in Spain and the proposal of action trends.